DHAMMONG : A RAIN RITUAL IN MADURA (A STUDY ON ITS HISTORY, FUNCTION, AND HISTOR ORY SIMBOLIC MEANING) - Nor Hasan; Edi Susanto (IBDA` : Jurnal Kajian Islam dan Budaya, 2020)
This article attempted to trace the existence of Dhâmmong tradition in the following scopes, namely: (1) Madurese perception against Dhâmmong , (2) the function and symbolic meaning of Dhâmmong in human life, and (3) the efforts of the Madurese community to preserve the Dhâmmong tradition. Through a descriptive phenomenological analysis, this study revealed that Dhâmmong is a hereditary tradition carried out by the Madurese community, it is urged by the community’s anxiety caused by the long dry season (némor lanjheng). Dhâmmong functionsas a means for salametan, paying respect for the ancestors, strengthening human relations (silaturrahim ), Bhek Rembhek, and nguri berkah (the fertility of the earth). The offerings and mouth-music by imitating the sounds of animals represent a strong desire and wishof the community for the immediate rainfall that could pour out blessings for the community. Hence, the community’s efforts to preserve Dhâmmong are: (1) introducing and involving the younger generation in the ritual, and (2) setting and changing the time sequence of Dhâmmong implementation from night to daytime.